COVID-19-related attitudes, risk perceptions, preventive behaviours and economic impact in sub-Saharan African countries: implementing a longitudinal phone-based survey protocol in rural Senegalese households - Gwenaëlle Maradan; Elhadji Ba; Assane Ndiaye; Cheikh Sokhna; Patrick Peretti-Watel; Valérie Seror; Sébastien Cortaredona; Jocelyn Raude; Olivier L’Haridon; Cyril Berenger; El-Hadj Ba (BMJ Open)
Introduction Rural areas are considered safe havens against the increased spread of COVID-19 and associated restrictive measures, especially in contexts where public authorities are not in a position to systematically and substantially ease COVID-19-induced economic shocks. In the current sub-Saharan Africa context, still marked by uncertainty surrounding the spread of COVID-19, we present the protocol of an ongoing longitudinal study aimed at investigating COVID-19-related attitudes, risks perceptions, preventive behaviours and economic impact in rural areas in Senegal.Methods and analysis A prospective randomised longitudinal study of 600 households located in three semiurban villages and nine randomly selected rural villages in the Niakhar area (located 135 km East of Dakar). Three ad hoc phone surveys are administered to 600 heads of households, their housewives in charge of managing the household and a relative living temporarily in the household, respectively. In addition to sharing identical sets of questions on several topics (risks perceptions, attitudes to curfew, attitudes to vaccines, beliefs about COVID-19 infection), the three separate survey questionnaires also include other topics (economic impact, local preventive strategies) whose related questions differ between questionnaires. As analysing evolutions is the study’s primary focus, data on all the topics covered will be collected in three waves unless the spread of COVID-19 by mid-2021 justifies extending data collection. The present article presents the study protocol and details about the implementation of the first wave of data collection which started in July 2020. The decision to wait before presenting the protocol was based on the unprecedented context the COVID-19 pandemic.Ethics and dissemination The survey’s protocol was approved by the Senegalese National Ethical Committee for Research in Health (131/MSAS/CNERS/Sec) and received authorisation from both the Senegalese Ministry of Health (619/MSAS/DPRS/DR) and the French Commission on Information Technology and Liberties (CNIL 2220771).